NON-BANKING FINANCIAL COMPANIES AND COMMERCIAL VEHICLE FINANCE: A STUDY IN THE MUMBAI REGION - Muduli, Kishore Chandra; Acharya, Prem Bhagwan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research explores the role and impact of Non-Banking Financial Companies (NBFCs) in providing commercial vehicle finance in the Mumbai region. It delves into the functioning, financing mechanisms, credit policies, customer satisfaction, and market outreach strategies employed by selected NBFCs. With commercial vehicles forming a backbone of trade and transport, especially in metropolitan cities like Mumbai, financing plays a pivotal role in their accessibility. This study aims to understand the strengths, challenges, and current trends influencing commercial vehicle financing by NBFCs, drawing insights from primary data and secondary sources. The findings offer critical suggestions for policy reforms and improved customer service delivery.